Urinary phytoestrogens and the risk of uterine leiomyomata in US women - Fang Yang; Youguo Chen (BMC, 2023)
Abstract Background Uterine leiomyomata (UL) is a common gynecological disease in women. Studied on the relationship between single metabolites of urinary phytoestrogens and UL, especially for the combined effects of mixed metabolites on UL still are insufficient. Methods In this cross-sectional study, we included 1,579 participants from the National Health and Nutrition Examination Survey. Urinary phytoestrogens were assessed by measuring urinary excretion of daidzein, genistein, equol, O-desmethylangolensin, enterodiol and enterolactone. The outcome was defined as UL. Weighted logistic regression was used to analyze the association between single metabolites of urinary phytoestrogens and UL. Notably, we adopted the weighted quantile sum (WQS) regression, Bayesian kernel machine regression (BKMR), and quantile g-computation (qgcomp) models, to investigate the combined effects of six mixed metabolites on UL. Results The prevalence of UL was approximately 12.92%. After adjusting age, race/ethnicity, marital status, drinking status, body mass index, waist circumference, menopausal status, ovary removed status, use of female hormones, hormones/hormone modifiers, total energy, daidzein, genistein, O-desmethylangolensin, enterodiol, and enterolactone, the association of equol with UL was significant [Odds ratio (OR) = 1.92, 95% confidence interval (CI): 1.09-3.38]. In the WQS model, mixed metabolites of urinary phytoestrogen had a positive association with UL (OR = 1.68, 95%CI: 1.12-2.51), with the highest weighted chemical of equol. In the gpcomp model, equol had the largest positive weight, followed by genistein and enterodiol. In the BKMR model, equol and enterodiol have positive correlation on UL risk, while enterolactone has negative correlation. Conclusion Our results implied a positive association between the mixed metabolites of urinary phytoestrogen and UL. This study provides evidence that urinary phytoestrogen-metabolite mixture was closely related to the risk of female UL.